2013
DOI: 10.3896/ibra.1.52.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Standard methods for artificial rearing ofApis melliferalarvae

Abstract: SummaryOriginally, a method to rear worker honey bee larvae in vitro was introduced into the field of bee biology to analyse honey bee physiology and caste development. Recently, it has become an increasingly important method in bee pathology and toxicology. The in vitro method of rearing larvae is complex and can be developed as an art by itself, especially if the aim is to obtain queens or worker bees which, for example, can be re-introduced into the colony as able members. However, a more pragmatic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
183
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 81 publications
4
183
1
1
Order By: Relevance
“…One of the main differences between our larval diet recipe and those listed in previous protocols (Aupinel et al, 2005;Crailsheim et al, 2013) are the increase in the water content and a reduction in the royal jelly content of diets A and B. We found that the diets noted in the literature (Aupinel et al, 2005;Crailsheim et al, 2013) were prone to drying out in the experimental conditions under which we reared larvae. Consequently, we increased the amount of water added to our diets over that recommended by Aupinel et al (2005) and Crailsheim et al (2013).…”
Section: Larval Diet Source and Compositionsupporting
confidence: 47%
See 3 more Smart Citations
“…One of the main differences between our larval diet recipe and those listed in previous protocols (Aupinel et al, 2005;Crailsheim et al, 2013) are the increase in the water content and a reduction in the royal jelly content of diets A and B. We found that the diets noted in the literature (Aupinel et al, 2005;Crailsheim et al, 2013) were prone to drying out in the experimental conditions under which we reared larvae. Consequently, we increased the amount of water added to our diets over that recommended by Aupinel et al (2005) and Crailsheim et al (2013).…”
Section: Larval Diet Source and Compositionsupporting
confidence: 47%
“…We provide an updated protocol with a revised method in a step-by-step format to outline how to rear honey bee workers artificially. The Crailsheim et al (2013) COLOSS BEEBOOK publication for the artificial rearing of honey bees provides guidance for understanding the historical context of the methodology and the different rearing approaches that are utilized by various researchers. The "standardized methods" are, however, difficult to follow and interpret for a researcher who is not familiar with the methodology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two day old worker honeybee larvae were grafted onto larval food in 48-well microtiter plates (Thermo Fisher Scientific, Rochester, New York), using a protocol slightly modified from Aupinel et al (2005); see also Crailsheim et al (2013). The grafted larvae were kept in an incubator (Memmert HCP 108, GmbH + Co. KG, Schwabach, Germany) under constant darkness at 34°C and 95% relative humidity (days 1 to 6).…”
Section: Larval Rearingmentioning
confidence: 99%